2006
DOI: 10.1097/01.hp.0000225466.45659.08
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Health Risks Associated With Occupational Radiation Exposure: Addressing Measurement Error and Minimum Detectable Exposure Level

Abstract: Occupational exposures are subject to several types of measurement errors. This paper considers two of the most common types of measurement error associated with occupational exposures: the error due to below minimum detection level and doses due to random measurement error. Doses are often recorded as zero when the exposure is below the minimum detection level. Values that are below the minimum detection level and are entered as zero lead to underestimation of the true exposure and can result in either an ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This variability can be attributed to a combination of variation in exposure levels over time and space. Advanced methodologies to acquire insight in the level of measurement variability on HOS outcomes have been proposed (Heederik and Miller 1988; Kromhout et al 1999; Loomis et al 1998; Xue et al 2006). Before the evaluation, risk assessors must define a minimum acceptable level of information required to assess whether enough insight in variability of exposure measurements is provided in HOS.…”
Section: Description Of the Framework And Evaluation Guidelinesmentioning
confidence: 99%
“…This variability can be attributed to a combination of variation in exposure levels over time and space. Advanced methodologies to acquire insight in the level of measurement variability on HOS outcomes have been proposed (Heederik and Miller 1988; Kromhout et al 1999; Loomis et al 1998; Xue et al 2006). Before the evaluation, risk assessors must define a minimum acceptable level of information required to assess whether enough insight in variability of exposure measurements is provided in HOS.…”
Section: Description Of the Framework And Evaluation Guidelinesmentioning
confidence: 99%
“…The most significant approach to reducing the overall uncertainty associated with the Doses-2005 analysis would involve the minimization of uncertainty in the urine bioassay analyses. A similar discussion regarding the effect of random measurement error on relative risk estimation was presented by Xue et al (2006). Unfortunately, the uncertainty associated with the previously obtained experimental data cannot be changed.…”
Section: Basic Uncertainty In the Dosementioning
confidence: 63%
“…Therefore, the risk reported in epidemiologic studies would be biased when the doses are only assessed based on the reported NDR doses, especially among irregular badge wearers. The underestimated doses caused by censoring of minimum detection limit doses resulted in the overestimation of the radiation exposure risk in the Canadian occupational radiation workers [ 13 ], while the risk for all-cause mortality in the United States (US) Oak Ridge National Laboratory radiation workers was not significantly altered after taking into consideration the random measurement error and missed doses due to falling below the minimum detection level [ 14 ]. The estimates of external radiation dose obtained from personal dosimeters have several quantifying sources of errors [ 15 ]; therefore, its influence on risk estimation could vary at different levels of exposure underestimation and needs to be evaluated in each epidemiological study.…”
Section: Discussionmentioning
confidence: 99%